A blood safety perspective on emerging arboviral infections in the United Kingdom - Rajendra, Piya; Secret, Shannah; Brailsford, Su; Golubchik, Tanya; Simmonds, Peter; Harvala, Heli (Wiley-Blackwell, 2026)
A core focus of the blood services is to maintain the blood supply whilst simultaneously being vigilant for potential threats to blood safety. At present, West Nile virus (WNV), Usutu virus (USUV), Dengue virus (DENV) and Tick-borne encephalitis virus (TBEV) are considered primary arboviral threats to blood safety in the UK and Northern Europe. Climate change and globalisation have enhanced the frequency of WNV and DENV cases being reported in Europe, furthering the likelihood of their spread to the UK. Furthermore, both TBEV and USUV have already been identified in reservoir hosts in England and the first human cases of TBEV infections acquired in England have been recently documented. Existing policy to protect the blood supply against emerging viral risks is based on donor deferral or nucleic acid test (NAT) screening for those recently returning from WNV endemic areas, only. Constant evaluation of the current policy is necessary to assess the feasibility of donor deferral if the case numbers within Europe continue to increase, and to determine if selective screening for these viruses is needed. Regardless of the testing and prevention strategies decided upon by the blood services, frequent review of these policies will be necessary to reflect the national and wider disease epidemiology of these arboviral infections.